2019
DOI: 10.1177/1609406919876469
|View full text |Cite
|
Sign up to set email alerts
|

The Boundaries of Research in an Authoritarian State

Abstract: This article provides a reflective analysis of a local scholar on methodological challenges of conducting research in Kazakhstan — a post-Soviet, authoritarian, Central Asian country. It specifically addresses the problems of getting access to government officials and the quality of data, describes the strategies applied by the researcher to mitigate these obstacles, and discusses the impact of the political environment on decisions relating to the research design, ethical integrity, safety of participants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The arrest of Canadian scholar Alexander Sodiqov in Tajikistan and other similar unvoiced cases illustrate the limitations, impediments, and even safety implications for both researchers and research participants in Central Asian countries (The Guardian, 2014). There are many problems related to research in 'closed contexts' such as poor state governance, lack of collaboration between ministries and departments, and access to reliable data and information (Janenova, 2019). Closed contexts here are referred to as 'authoritarian', 'illiberal', or 'tightly-controlled' (Koch, 2013a;p.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The arrest of Canadian scholar Alexander Sodiqov in Tajikistan and other similar unvoiced cases illustrate the limitations, impediments, and even safety implications for both researchers and research participants in Central Asian countries (The Guardian, 2014). There are many problems related to research in 'closed contexts' such as poor state governance, lack of collaboration between ministries and departments, and access to reliable data and information (Janenova, 2019). Closed contexts here are referred to as 'authoritarian', 'illiberal', or 'tightly-controlled' (Koch, 2013a;p.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to other countries, Kazakhstan raised the issue of open data quite late, and only in 2015 adopted the Law on Access to Information . Notwithstanding the existing legislation, "statistical data can be unreliable as the government officials tend to portray "a better picture" to suit the political leadership and international community," says Janenova (Janenova, 2019). There have been cases where secondary data provided by authorities of Kyrgyzstan, Kazakhstan, and Uzbekistan demonstrated alternating content compared to those by international organizations, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A fourth challenge is lack of access to officials and prospective research participants. ‘Getting access to the government officials can be a frustrating, long, and disappointing process, posing many bureaucratic obstacles’ (Janenova, 2019, p. 3). For survey and focus group studies, Janenova (2019) found that prospective respondents ‘might initially agree, then keep postponing, and changing the date of the interview giving various reasons, and finally, refuse at the last minute … or keep delaying it in the hope that the researchers would stop their attempts’.…”
Section: Barriers Confronting Scholars Of Central Asian Jandmcmentioning
confidence: 99%
“…Despite several rounds of civil service and administrative reforms over the last three decades, all Central Asian countries suffer from rampant corruption, Soviet legacy, excessive bureaucracy, and a high degree of politisation (Knox and Janenova, 2019). Access to official data in Central Asia is highly restricted for scholars, available statistical data might be unreliable, as well as policy consultation and policy evaluation are rarely conducted to avoid any potential risks for senior officials (Janenova, 2019). In summary, Central Asia presents a highly challenging context for public administration as an academic discipline: a context which is not tolerant of any criticism towards the government and open expression of views questioning the rationale for political directives from the top.…”
Section: Authoritarian Context Of Central Asia For Teaching Public Admentioning
confidence: 99%